An Analysis of Students’ Perception Toward the Use of Narrative Text in Writing Activities in English Student Community - Marisa Sandika; Fera Zasrianita; Hanura Febriani (Journal of Innovation in Teaching and Instructional Media, 2025)
Writing in English is often challenging for students, especially in organizing ideas, developing coherence, and applying accurate grammar. Narrative text, although commonly introduced in language classes, has not been fully explored as a medium to foster creativity and strengthen writing competence in student-led communities. This study aims to analyze students’ perceptions of the use of narrative text in writing activities at the English Students Community (ESCO) of the English Study Program, Fatmawati Sukarno State Islamic University Bengkulu. Using a qualitative descriptive method, data were obtained from 39 fourth-semester students through questionnaires and in-depth interviews. The findings indicate that most students perceived narrative text writing as useful for generating ideas, structuring paragraphs, enriching vocabulary, and improving grammar mastery. Participation in narrative-based writing activities also increased students’ motivation and confidence in both spoken and written English. However, some challenges were reported, such as difficulties in plot development, character creation, conflict resolution, vocabulary limitation, and time management. In conclusion, narrative text provides not only academic benefits but also motivational value, encouraging students to be more active in writing practices. This study suggests the importance of providing guidance in story construction, incorporating peer feedback, and strengthening writing communities as a way to enhance English proficiency.